The Application of AI Technology in China's Douyin Live Commerce and Its E-commerce Strategy in a Cross-cultural Context - An Australian Example - Xue, Shan (Transactions on Economics, Business and Management Research, 2024)
This paper explores the future business strategies of cross-border e-commerce companies from China using AI technology to apply the live commerce practice based on the TikTok platform in the Australian market. Throughout the literature review, this paper lists the existing studies about the factors influencing consumers' preference for live commerce and the application of AI technology. Based on the Chinese market, these studies' results provide a transferable experience for the Australian market. On top of that, the use of AI technology allows for 24/7 live streaming of products, reducing labour costs and broadening the reach of live streaming. It also allows virtual streamers to perform better than real people in terms of consistency and accuracy of the information they present. However, Australian consumers have low trust in AI because they are highly concerned about data privacy. Based on the above research, this paper proposes business strategies for cross-border e-commerce companies from China using AI technology to enter the Australian market using the SWOT model. Also, there are recommendations to help these companies succeed in the Australian market in live commerce.